Quality control based on electrical resistivity measurements - Ferreira, Rui Miguel (2006)
The electrical resistivity of concrete is one of the main parameters controlling the initiation and propagation of reinforcement corrosion. It is common knowledge that concrete electrical resistivity is mainly dependent on the w/c ratio (pore connectivity), volume and type of cement, temperature and the moisture. This research work studies the effect of specimen shape and temperature of measurement on electrical resistivity measurements of concrete using the four-point Werner electrode. In addition, the estimation of future values based on early age measurements is also studied. Research has indicated that there is a strong relationship between electrical resistivity and durability indicators at a given age. A relationship for the estimation of the electrical resistivity using early age measurements is suggested. Furthermore, it was observed that temperature has a significant influence on the electrical resistivity of concrete. Based on test results, a relationship similar to the Arrhenius equation is also suggested that can be used for conversion of electrical resistivity measurements to a reference temperature. Based on these equations, the electrical resistivity and compressive strength of concrete at 28 days is predicted using values of electrical resistivity of up to 7 days. Errors depend on the equation used but are approximately 5 % for estimates up to 28 days.